2019
DOI: 10.3390/app9071446
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of GPS Water Vapor Tomography for Maximizing the Use of Signal Rays

Abstract: The spatio-temporal distribution of atmospheric water vapor information can be obtained by global positioning system (GPS) water vapor tomography. GPS signal rays pass through the tomographic area from different boundaries because the scope of the research region (latitude, longitude, and altitude) is designated in the process of tomographic modeling, the influence of the geographic distribution of receivers, and the geometric location of satellite constellations. Traditionally, only signal rays penetrating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The technique, apart from being more efficient computationally, improved the results in some cases with respect to other methods. A different method by Yang et al [38] tried to maximize the number of rays by considering water vapor density in the upper region outside the boundaries as four (one per direction) new parameters to obtain. This addition to the traditional method allowed the use of rays that do not come from the top boundary of the study region, but from the sides.…”
Section: Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…The technique, apart from being more efficient computationally, improved the results in some cases with respect to other methods. A different method by Yang et al [38] tried to maximize the number of rays by considering water vapor density in the upper region outside the boundaries as four (one per direction) new parameters to obtain. This addition to the traditional method allowed the use of rays that do not come from the top boundary of the study region, but from the sides.…”
Section: Tomographymentioning
confidence: 99%
“…An experiment in Hong Kong was carried out to test this method, showing better results than traditional tomography. Yang et al [38] also showed that, to improve tomography, it is more relevant to increase the number of voxels crossed by rays than than increasing the number of rays. However, the number of possible approaches is large and, therefore, Brenot et al [39] compared several variations of approaches to tomographic techniques with radiosonde and ECMWF reanalysis.…”
Section: Tomographymentioning
confidence: 99%
“…The situations described above lead to an ill-conditioned GNSS tomographic model, i.e., the singularity condition, in which an ill-posed problem appears in the inversion of the tomographic equations, so the inverse of the design tomographic matrix cannot be directly obtained [6,7,9,29,30]. Several methods have been developed for solving the ill-posed problem, such as (1) adding inter-spatial constraints [6,8,12,13,[31][32][33][34][35]; (2) adding prior information of WV [31,[36][37][38]; (3) expanding the tomographic area to increase the number of available observations [19,37,[39][40][41][42]; (4) using multi-GNSS observations [41,[43][44][45][46][47]; (5) utilizing other observations [18,[48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Haji-Aghajany et al (2020b) reduce the number of unknown parameters and empty voxels by merging voxels based on the WRF model, which improves the ill-conditioned tomographic equations. In addition, the studies in Yang et al (2019), , Zhao et al (2018), Zhao et al (2020), and Zhang et al (2020b) propose approaches to incorporate the GNSS signals passing through the side face of the tomography area. Zhao et al (2019) utilize observations of GNSS stations located outside the study area, which increases the number of the crossed voxels and the accuracy of the tomography results.…”
Section: Introductionmentioning
confidence: 99%